A review on cobia, Rachycentron canadum, aquaculture - Daniel D. Benetti; Jorge Suarez; Julio Camperio; Ronald H. Hoenig; Carlos E. Tudela; Zack Daugherty; Charles J. McGuigan; Shubham Mathur; Luiz Anchieta; Yole Buchalla; Jorge Alarc on; Dario Marchetti; et al. (Wiley, 2025)
Cobia, Rachycentron canadum, is an important species for aquaculture worldwide. Production technology from egg to market was established in the early 1990s and continues to be perfected to this day. This species exhibits extraordinary scope for growth and can reach between 4 and 8 kg in 1 year, with females growing almost twice as fast and large as males. Despite continuous progress in maturation, spawning, larval rearing, fingerling production, nutrition, health management, genetics, and growout technology, overall cobia aquaculture production worldwide has been slow in the last decade. One of the biggest challenges remains the development of practical commercial feeds that are ecologically and economically efficient for this species. Feed conversion ratios are still very high, ranging from 2.0 to 3.0:1. In addition to nutritional challenges, diseases such as Photobacterium, Amyloodinium ocellatus, and Brooklynella hostilis continue to impact cobia aquaculture production worldwide. Genetics and breeding programs for cobia are still at their infancy. We report on current status of cobia breeding efforts as well as on advances on developing female monosex populations to exploit the sexually dimorphic growth in this species. Nutrition, health, and genetics will be the greatest drivers to improve overall performance and increases in production of the cobia aquaculture industry.